الصوت والصورة ومدى الاعتداد بهما في الإثبات الجنائي (El-Wahat Journal for Research and Studies, 2021)
Evidence and disclosure of the truth is one of the most important issues of concern to the judge to establish sufficient evidence to the commission of the crime and to assign it to the perpetrator, because the right without evidence is nothing.In view of the decline of traditional means and means of proof in proving crimes, harnessing the use of modern scientific means of proof based on scientific arguments is now more than a necessity. Despite the fact that these means, whatever the strength of their argument, require a judicial sense that only the judge has, which serves the case, satisfies justice and achieves the desired goal, in condition of being providedwith differentscientific knowledge so that he can understand and exploit it properly. Keywords -Image, Sound, Crime, Criminal Evidence.